Virulence of oomycete pathogens from Phragmites australis‐invaded and noninvaded soils to seedlings of wetland plant species - Crocker, Ellen V.; Karp, Mary Ann; Nelson, Eric B. (Ecology and evolution, 2015)
Soil pathogens affect plant community structure and function through negative plant–soil feedbacks that may contribute to the invasiveness of non‐native plant species. Our understanding of these pathogen‐induced soil feedbacks has relied largely on observations of the collective impact of the soil biota on plant populations, with few observations of accompanying changes in populations of specific soil pathogens and their impacts on invasive and noninvasive species. As a result, the roles of specific soil pathogens in plant invasions remain unknown. In this study, we examine the diversity and virulence of soil oomycete pathogens in freshwater wetland soils invaded by non‐native Phragmites australis (European common reed) to better understand the potential for soil pathogen communities to impact a range of native and non‐native species and influence invasiveness. We isolated oomycetes from four sites over a 2‐year period, collecting nearly 500 isolates belonging to 36 different species. These sites were dominated by species of Pythium, many of which decreased seedling survival of a range of native and invasive plants. Despite any clear host specialization, many of the Pythium species were differentially virulent to the native and non‐native plant species tested. Isolates from invaded and noninvaded soils were equally virulent to given individual plant species, and no apparent differences in susceptibility were observed between the collective groups of native and non‐native plant species. We examined the diversity and virulence of soil oomycete pathogens in wetland soils invaded by non‐native Phragmites australis (European common reed) to better understand the potential impacts of invasive plant species on soil pathogen communities and the potential feedback of these pathogen species to influence invasive success. We isolated oomycetes from four sites over a 2‐year period, collecting nearly 500 isolates belonging to 36 different species. Many of the Pythium species were differentially virulent to a range of native and non‐native plant species and isolates from invaded and non‐invaded soils exhibited similar levels of virulence to individual plant species with no apparent differences between native and non‐native plant species were observed.